The Rho GTPase exchange factor Vav2 promotes extensive age-dependent rewiring of the hair follicle stem cell transcriptome - Lorenzo-Martín, L. Francisco; Bustelo, Xosé R. (Frontiers in Cell and Developmental Biology, 2023)
Both the number and regenerative activity of hair follicle stem cells (HFSCs) are regulated by Vav2, a GDP/GTP exchange factor involved in the catalytic stimulation of the GTPases Rac1 and RhoA. However, whether Vav2 signaling changes in HFSCs over the mouse lifespan is not yet known. Using a mouse knock-in mouse model, we now show that the expression of a catalytically active version of Vav2 (Vav2Onc) promotes an extensive rewiring of the overall transcriptome of HFSCs, the generation of new transcription factor hubs, and the synchronization of many transcriptional programs associated with specific HFSC states and well-defined signaling pathways. Interestingly, this transcriptome rewiring is not fixed in time, as it involves the induction of 15 gene expression waves with diverse distribution patterns during the life of the animals. These expression waves are consistent with the promotion by Vav2Onc of several functional HFSC states that differ from those normally observed in wild-type HFSCs. These results further underscore the role of Vav2 in the regulation of the functional state of HFSCs. They also indicate that, unlike other Vav2-dependent biological processes, the signaling output of this exchange factor is highly contingent on age-dependent intrinsic and/or extrinsic HFSC factors that shape the final biological readouts triggered in this cell type.